ANALISIS YURIDIS PELANGGARAN MEREK HELP YANG DIGUNAKAN TANPA IZIN OLEH PIHAK LAIN (STUDI PUTUSAN NOMOR 24/PDT.SUS-MEREK/2021/PN.NIAGA.JKT.PST) - Franky, Franky; Bustani, Simona (Fakultas Hukum Universitas Trisakti, 2023)
Trademark infringement occurs because there is a similarity in substance or in its entirety to a brand, as is the case in case Number 24/Pdt.Sus-Merek/2021/PN.Niaga.Jkt.Pst. Problems 1) What are the regulations for the protection of rights holders of the HELP brand whose marks are used by other parties based on Law no. 20 of 2016 concerning Brands and Geographical Indications?. 2) Is the Commercial Court judge's decision regarding the HELP trademark dispute in accordance with Law no. 20 of 2016 concerning Brands and Geographical Indications?. This research is of the normative type with the nature of descriptive research with secondary data carried out by literature study and then carried out qualitative analysis and deductive logic to draw conclusions. The results of the research can be seen. Legal protection against Melia Lustojoputro as the owner of the rights to the